The trans-contextual model: Perceived learning and performance motivational climates as analogues of perceived autonomy support - Barkoukis, V.; Hagger, Martin (Springer, 2013)
The trans-contextual model of motivation (TCM) proposes that perceived autonomy support in physical education (PE) predicts autonomous motivation within this context, which, in turn, is related to autonomous motivation and physical activity in leisure-time. According to achievement goal theory perceptions of learning and performance, motivational climate in PE can also affect autonomous motivation in PE. The purpose of the present study was to examine the influence of an integrated approach of perceptions of motivational climate in PE by incorporating aspects of perceptions of motivational climate from achievement goal frameworks on autonomous motivation in PE within the TCM. High school students (N = 274) completed self-report measures of perceived autonomy support, perceived learning, and performance motivational climate and autonomous motivation in PE. Follow-up measures of autonomous motivation in a leisure-time context were taken along with measures of attitudes, subjective norms, perceived behavioural control and intentions from the theory of planned behaviour 1 week later. Self-reported physical activity behaviour was measured 5 weeks later. The results of the path analyses indicated that perceived learning climate was the strongest predictor of autonomous motivation in PE and leisure-time contexts and mediated the effect of perceived autonomy support on autonomous motivation in PE. Perceived performance climate showed no significant effect on autonomous motivation in PE and leisure-time. Results also confirmed the premises of TCM regarding the effect of autonomous motivation in leisure-time on leisure-time physical activity and the mediating role of the planned behaviour theory variables.